Optimasi Bio-char Hasil Proses Katalitik Pirolisis Palm Kernel Expeller (PKE) Menggunakan Katalis NiMo/NZA dengan Pendekatan RSM - Sihotang, Fernando; Bahri, Syaiful; Saputra, Edy (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2025)
The increasing demand for renewable energy sources has driven interest in biomass-based alternatives, particularly bio-char derived from palm kernel expeller (PKE), an abundant by-product of Indonesia’s palm oil industry. This study aims to optimize bio-char production through catalytic pyrolysis of PKE using a NiMo/NZA catalyst, employing a Response Surface Methodology (RSM) with a Box-Behnken design. Key variables investigated include T (°C) (400–500 °C), catalyst loading (2–6%), and metal loading (0–4% wt). The NiMo/NZA catalyst was synthesized through acid activation, metal impregnation, and thermal treatment, and its structure was confirmed using FTIR analysis. Pyrolysis experiments were conducted in a fixed-bed reactor under nitrogen and hydrogen atmospheres. The highest bio-char yield of 39.38% was obtained at 400 °C with 2% catalyst and 4% metal loading. Optimization modeling using Minitab v.22 indicated that the optimal conditions were at 400 °C, 6% catalyst, and 2.91% metal loading, resulting in a predicted yield of 36.82% with a desirability of 0.979. Statistical analysis showed a significant influence of catalyst and metal loading over temperature on bio-char yield (p-value < 0.05; Adjusted R² = 0.9236). These results support the potential of catalytic pyrolysis with tailored catalysts to enhance bio-char production from palm biomass, contributing to waste valorization and renewable fuel development.